Review of Apistus (Synanceiidae: Apistinae) with description of a new species from the Arabian Sea and taxonomic status of Apistus balnearum Ogilby 1910, a junior synonym of Apistops caloundra (De Vis 1886) - Matsunuma, Mizuki; Seah, Ying Giat; Motomura, Hiroyuki (Ichthyological research, 2025)
A taxonomic revision of the genus Apistus (family Synanceiidae), previously regarded as monotypic, including only Apistus carinatus (Bloch and Schneider 1801), resulted in the recognition of two species, including a new species from the Arabian Sea, Apistus shaula sp. nov. The following seven nominal species are regarded as junior synonyms of A. carinatus, as determined in previous studies: Apistus alatus Cuvier 1829, Apistus israelitarum Cuvier 1829, Parapistus marmoratus Steindachner 1866, Apistus evolans Jordan and Starks 1904, Apistus venenans Jordan and Starks 1904, Apistus faurei Gilchrist and Thompson 1908, and Apistus macrolepidotus Ogilby 1910. Apistus shaula sp. nov. is characterized by numerous black spots on the inner surface of the pectoral fins (absent in A. carinatus) and relatively longer 1st to 5th dorsal-fin spines compared with A. carinatus. Although Apistus balnearum Ogilby 1910 has been regarded as a junior synonym of A. carinatus, two juvenile syntypes possessed five mandibular barbels (three in Apistus) and were therefore identified as Apistops caloundra (De Vis 1886).